The prevalence of musculoskeletal discomfort among female wearing different heights and shapes of heel shoes in Kuantan - Zainudin, Athirah; Zamli, Zaitunnatakhin (UPM Press, 2017)
The trend of wearing high heels is not restricted only to adult females but also involved females at all ages. In fact, women preferred to wear high heels for some reason although many studies found that this habit can cause physical and functional abnormalities to the lower and upper limbs. The trend of wearing high heels is not only important as a part of clothing but also reflects their personality, confidence and professionalism. Nevertheless, the past shoe wearing behavior may develop musculoskeletal discomfort (MSD) among heel shoes wearers. Thus, this study aims to determine the prevalence of MSD and its association with the risk factors, shoe designs and past shoe behaviors among female wearing heel shoes in Kuantan, Pahang. A cross sectional study was performed and subjects were recruited by using a purposive sampling. A self-administered questionnaire was given, and the height and shape of the heels were measured. The prevalence of MSD was calculated and association with the risk factors, shoe designs and past shoe behaviors were determined. The data showed that the overall prevalence of MSD among female wearing heeled shoes was 67.1%. The prevalence was slightly higher in the high-heel (68.2%) than the low-heel group (66.7%). Surprisingly, the prevalence of MSD among female wearing dress shoes (68.0%) and wedges (67.3%) was greater than those who worn stilettos (50.0%). However, none of the shoe designs showed significant different between the groups. Among these participants, they felt uncomfortable in the lower leg and ankle, and apart of all the factors examined, there was significant association between MSD with duration of wearing heel shoes (r = 0.223, p-value= 0.049). Since prolonged wearing high heels can interfere walking ability, public awareness campaigns should stress on the important of wearing the right shoe for the right activity.